Antisera recognising HLA-A, -B and DRW antigens raised in rhesus monkeys. - Barnstable, C; Snary, D; Crumpton, M; Balner, H; Bodmer, W (1980)
Rhesus monkeys were immunized with partially purified HLA-A, -B, -C and DR antigens. The resulting sera were shown to have activity against species-specific determinants on both HLA-A, -B, -C chains and beta 2 microglobulin by the use of somatic cell hybrids. When this was removed by absorption, the sera showed activity against three of the four HLA-A and -B antigens in the immunogen when tested on a panel of peripheral blood lymphocytes and T cells. Antibodies recognizing HLA-DR antigens were detected by testing platelet absorbed sera on a panel of typed lymphoblastoid cell lines. After absorption to remove activity against species-specific determinants on the HLA-DR antigens, two cross reacting specificities were defined. One consisted of a determinant in common between HLA-DRw1, 2 and 6 and the other a putative determinant in common between HLA-DRw4, and 5. The nature and significance of these cross-reacting groups of HLA-DR antigens is discussed in the light of current HLA-DR serology and the nature of HLA antigens in general.